Human Existence And Social Anthropological Characteristics - Ergashev Ozodbek Shavkatovich (Genius Journals, 2023)
The article seeks to prove the thesis about the significance and importance of historical anthropological theories and methodological approaches aimed at understanding the meanings, essence and value systems of past human existence for philosophical anthropology. The study of this problem is relevant for understanding the evolution of human identity with philosophical and anthropological concepts, the essence of one's existence and the relationship to the world. Methodological approaches and concepts of modern historical anthropology form the basis of mental reconstruction and understanding of the mental and cultural causes and factors of human existence due to the analysis of the evolution of different forms of worldview, behavior, worldview, individual and social activity. of the person
Keywords: Human being; historical anthropology; philosophical anthropology